MODEL PENGEMBALIAN ASET (ASSET RECOVERY) SEBAGAI ALTERNATIF MEMULIHKAN KERUGIAN NEGARA DALAM PERKARA TINDAK PIDANA KORUPSI - Fatin Hamamah; Heru Hari Bahtiar (IAIN Syekh Nurjati Cirebon, 2019)
Corrupted state assets not only narrowly affect the state, but also harm the state and its people. The formal procedural approach through the current criminal procedure law has not been able to recover state losses. Whereas the state loss caused by corruption is a state asset that must be saved. Therefore, another way is needed to save the country's assets. Namely the return of assets of perpetrators of criminal acts of corruption (asset recovery). When looking at the country from the perspective of the victim, the state must obtain protection, in this case recovery from the losses suffered due to corruption. the guilty wrongdoing and the application of substitute criminal penalties as additional crimes and through civil lawsuits by optimizing the role of the state attorney's attorney